União entre pessoas do mesmo sexo no Brasil : discursos em torno da ação direta de inconstitucionalidade 4.277 - Vijales, Fabricio Marcelo (2016)
Our goal is to analyze, in the speeches around the Supreme Court’s decision on homoerotic relationships, the articulation of ideologies and advances in the perspective of recognition of these relationships in Brazil. The research is built on the theory of labeling, demonstrating how the deviation is built through the implementation of concepts of normality in society, defining the relationship between people of the same sex as an abnormality. The speeches are analyzed through the Critical Discourse Analysis, focusing on forms of abuse of power to analyzing how discourses are inserted in society and result in social inequalities. The goal is to analyze, in the polarization of groups, how the progressive and conservative discourses articulate recognition of marriage between same sex, or defines it as a deviation from the traditional notion of family. Through the discourse analysis this study seeks to deepen, critically, the procedures of the action of developing the labeling, through the production of oral and written discourses, by which interpretations are built and shared by the institutions and social forces in the construction of the relationship between people of the same sex as a deviation.